Alterações nos teores de compostos bioativos, na capacidade antioxidante e na atividade fenilalanina amônia liase em uvas 'Isabel' tratadas com radiação UV-C - Maurer, Luana Haselein (2014)
Ultraviolet light type C (UV-C) is a non-thermal technology that has been used as an abiotic stressor to delay microbial growth and enhance the phytochemical content of food crops. However, its effects may vary depending on the cultivar, fruit, hormetic dose and time after exposure. Isabella is a hybrid grape cultivar (Vitis labrusca L.) that represents about 50% of Brazilian grape production and is commonly consumed in natura. The effects of UV-C irradiation (0.5, 1.0, 2.0, and 4.0 kJ m-2) followed by storage at 20°C (1, 3, and 5 days) were evaluated on quality indicators, bioactive compounds, antioxidant capacity and phenylalanine ammonia lyase (PAL) activity of Isabella grapes. The highest UV-C doses (2.0 and 4.0 kJ m-2) led to a rapid increase (about 10%) of total soluble solids (TSS) and decrease of pH values (p<0.05). All samples showed an increase on total phenolics (813.6 ± 99.6 in the 1st day vs. 1016.4 ± 79.6 mg gallic acid equivalents 100 g-1 skin FW in the 5th day), flavonols (351.1 ± 58.4 in the 1st day vs. 496.9 ± 83.1 mg quercetin-3-rutinoside equivalents 100 g-1 skin FW in the 5th day), and anthocyanins (215.3 ± 35.4 in the 1st day vs. 272.2 ± 43.5 mg malvidin-3-glucoside equivalents 100 g-1 skin FW in the 5th day) content along the storage (p<0.05). Total phenolic compounds increased after UV-C at 1.0 and 2.0 kJ m-2, whereas anthocyanin content increased after UV-C at 0.5, 1.0, and 2.0 kJ m-2 (p<0.05). The levels of ascorbic acid (AA) and total vitamin C decreased in all samples during the storage (p<0.05). UV-C treatment had no effect on the flavonol content, but decreased AA and total vitamin C content (0.5 - 2.0 kJ m-2, p<0.05). PAL activity decreased along storage time in all samples (47.7 ± 3.6 in the 1st day vs. 38.4 ± 2.7 and 32.4 ± 2.1 104 EAU min-1 mg protein-1 in 3rd and 5th days after treatment, p<0.05). UV-C radiation (0.5-2.0 kJ m-2) increased PAL enzyme activity in two-fold relation to control. UV-C treated grapes had higher antioxidant capacity than control grapes in the ferric reducing antioxidant power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays (p<0.05). Indeed, this effect was positively correlated to the content of total phenolic and anthocyanin compounds and negatively correlated to ascorbic acid and vitamin C contents (p<0.05). Thus, UV-C radiation can be used to increase bioactive compounds and antioxidant capacity of Isabella grapes, being 1.0 kJ m-2 the most appropriate dose for the studied conditions. UV-C effects appeared immediately after the irradiation and gradually decreased along the storage.